Use of ozone and ozonated growth factors in musculoskeletal disorders of the canine species (Ozone Therapy Global Journal, 2013)
Symptoms such as pain, lameness, muscle weakness, decreased activity, etc are partof daily practice in veterina ry clinics. The standar d therapies including antiinflammatories,anal ges i cs or su rgery and ot hers, improve or resolve proble msnormally, but sometimes the side effects of these therapies prevent their use. On theother hand, their high costs discourage the owner from using them. Ozone treatmentsin human medicine has been well documented and scientifically corroborated yearsago. Good examples of this are the large number of publications and the quality of thespecialized conferences. In veterinary medicine we still have a long way to go.The purpose of this work was to study the anti-inflammatory and analgesic effects ofthe ozone an d of the growth factors platelet-derived with activated ozone in can inespecies. The animals were divided into two groups; in group 1 were placed animalsdiagnosed with osteoarthritis, in group 2 were animals with spinal pain or pain in theextremities.In group 1, the animals were treated with ozone and growth factors and in group 2with ozone only.In group 1, 85% showed a significant improvement and in group 2,about 93%.This study shows an open door to a whole new world for the application ofozone therapy in veterinary medicine.